2+3(n-6)=4(n+2)-21

Simple and best practice solution for 2+3(n-6)=4(n+2)-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+3(n-6)=4(n+2)-21 equation:


Simplifying
2 + 3(n + -6) = 4(n + 2) + -21

Reorder the terms:
2 + 3(-6 + n) = 4(n + 2) + -21
2 + (-6 * 3 + n * 3) = 4(n + 2) + -21
2 + (-18 + 3n) = 4(n + 2) + -21

Combine like terms: 2 + -18 = -16
-16 + 3n = 4(n + 2) + -21

Reorder the terms:
-16 + 3n = 4(2 + n) + -21
-16 + 3n = (2 * 4 + n * 4) + -21
-16 + 3n = (8 + 4n) + -21

Reorder the terms:
-16 + 3n = 8 + -21 + 4n

Combine like terms: 8 + -21 = -13
-16 + 3n = -13 + 4n

Solving
-16 + 3n = -13 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-16 + 3n + -4n = -13 + 4n + -4n

Combine like terms: 3n + -4n = -1n
-16 + -1n = -13 + 4n + -4n

Combine like terms: 4n + -4n = 0
-16 + -1n = -13 + 0
-16 + -1n = -13

Add '16' to each side of the equation.
-16 + 16 + -1n = -13 + 16

Combine like terms: -16 + 16 = 0
0 + -1n = -13 + 16
-1n = -13 + 16

Combine like terms: -13 + 16 = 3
-1n = 3

Divide each side by '-1'.
n = -3

Simplifying
n = -3

See similar equations:

| 20x-8-12x+3=21x-9-13x+14 | | 15(-4g+8)+6=-1-(9-8g) | | 5p+14=8p(-2) | | 60n^2+258n+168=0 | | 2X^3-3X^2-3=0 | | 5.3x-3.24=3.18-5.4x | | 5p+14=8p-(-2) | | -3x+3=-33 | | 2.1x-5.25=3.15-3.5x | | 9x+7=6x+8 | | 2.1x-5.25=3.15-3.5 | | -7x-12+20x=14-12x+25x-10 | | 5x^2+46x-40=0 | | 3n+7=5n+3 | | 9x+5y=11x-8y | | 3x-5+1=-2x+7 | | 7+9(x-3)=1-6(x-9) | | 9y+5x=11y-8x | | 6y+5=11y+30 | | (-12a)(ab)=0 | | 18x^2-72x+40=0 | | (-12abc)(4ab)=0 | | 2(x-5)=-10+2x | | 150=4x-160 | | 5*0+4y=0 | | 0=4x^2-14x+3 | | 2+5(x-8)=11-7(x-7) | | 3n+4=3n+5 | | 6x+8=10x-40 | | 2x^2+12x=-110 | | (3x-7m)(5x+3m)= | | 7+(-2)+5= |

Equations solver categories